The Influence of Transformational Leadership and Employee Training on Employee Performance of Food and Beverage Small Enterprises - Rizqullah, Muhammad Zahran; Noermijati, Noermijati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The purpose of this study was to examine the relationship between transformational leadership and employee training, and their impact on employee performance in small enterprises within the food and beverage sector in the Lowokwaru sub-district of Malang city. Employing an explanatory and quantitative approach, the research utilized a purposive sampling method, involving 116 employees from small food and beverage enterprises as the total sample. Questionnaires were distributed offline to gather data. The collected data were processed using Statistical Product and Service Solutions (SPSS) 26, and hypotheses were tested through t-test and multiple linear regression. The findings of this study reveal that both transformational leadership and employee training exert a positive and significant influence on employee performance in small enterprises in the food and beverage sector located in Lowokwaru sub-district of Malang city. Abstrak Tujuan dari penelitian ini adalah untuk mengetahui hubungan transformational leadership dan employee training mempengaruhi employee performance pada usaha kecil makanan dan minuman di kecamantan Lowokwaru, kota Malang. Untuk mengetahui bagaimana variable-variabel tersebut berhubungan satu sama lain, penelitian ini menggunakan pendekatan eksplanatori dan kuantitatif. Penelitian ini dilakukan menggunakan metode purposive sampling dengan 116 karyawan perusahaan kecil makanan dan minuman menjadi sampel total, dan kuesioner didistribusikan secara luring. Untuk mengolah data yang dikumpulkan, Statistical Product and Service Solutions (SPSS) 26 telah digunakan, dan hipotesis diuji dengan uji t dan regresi linear berganda. Penelitian ini menunjukkan bahwa transformational leadership dan employee training memiliki efek positif dan signifikan terhadap employee performance pada usaha kecil makanan dan minuman di kecamatan Lowokwaru, kota Malang.